2008
DOI: 10.1179/174328408x323113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gauge length in superplastic tensile tests

Abstract: There is an incentive to obtain data on the mechanical behaviour of superplastic materials to model superplastic forming processes, in particular to help reduce forming times. The usual method involves tensile tests at elevated temperatures without extensometry. However, inhomogeneous deformation has a large effect on the apparent stress-strain behaviour and elongation to failure. Strain distributions have been measured in tensile specimens of superplastic Al-4?5Mg alloy with different gauge lengths, and on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…This could be attributed to the higher material flow to gauge length ratio, since the latter means an effectively wider gauge. Although the effect is small here, it agrees with the results presented by Bate et al [13], where specimens with smaller gauge length were shown to exhibit higher stress/strain curves. The three specimen geometries they considered showed more prominent disparities mainly because of their low gauge length to width ratio (1, 2 and 4), which meant high Fig.…”
Section: Combined Effects Of Gauge Length/widthsupporting
confidence: 93%
See 2 more Smart Citations
“…This could be attributed to the higher material flow to gauge length ratio, since the latter means an effectively wider gauge. Although the effect is small here, it agrees with the results presented by Bate et al [13], where specimens with smaller gauge length were shown to exhibit higher stress/strain curves. The three specimen geometries they considered showed more prominent disparities mainly because of their low gauge length to width ratio (1, 2 and 4), which meant high Fig.…”
Section: Combined Effects Of Gauge Length/widthsupporting
confidence: 93%
“…Their efforts concluded with an improved geometry that provides a constant strain rate in a major portion of the specimen's gauge. Bate et al [13], on the other hand, explored the geometry's impact on deformation homogeneity and stress/ strain curves, considering three AA5083 specimens with different gauge length-to-width ratios. They proposed a correction to stress/strain curves as a means to overcome the geometry's effects, particularly the associated material flow issue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specimen dimensions also influence the tensile strength and ductility of the material. As the gauge length increased, it reduced the effect of localised deformation at necking on total elongation; i.e., by increasing the gauge length percentage elongation of the specimen is further reduced [35]. The strain-hardening capacity of material also has impacts on the percentage elongation.…”
Section: Tensile Propertiesmentioning
confidence: 97%
“…The research found the significant increase in tensile and yield strengths of the material whereas a decrease in the ductility [34]. The mechanical properties of superplastic materials were investigated on superplastic Al-4·5Mg alloy with different gauge lengths and elongation was found to increase to double when gauge length to width ratio reduced 4 to 1 [35]. The ultimate tensile and yield strengths of steel weld metals decreased but the impact strength of weld metals increased by Ni additions in a controlled manner with respect to Mn .…”
Section: Tensile Propertiesmentioning
confidence: 99%